First 100 days : Onboarding a controller - Salo, Matti (My University, 2019)
The objective of this thesis is to describe the onboarding process of a newly hired management ac- counting professional, a controller. The goal is to identify challenges within the onboarding process and to find suggestions on how the onboarding process could be improved to achieve better out- comes for both the individual and the hiring organisation. The goal is also to align and understand the connection between the recommendations in the existing onboarding literature and the identified role of a controller based on earlier management accounting research. The motivation to study the onboarding process of a controller is to help provide recommenda- tions to practitioners on how to organise an effective onboarding process. There is a significant amount of literature on the role and the changes in the role of a controller already available, and this is true for onboarding as a process, but there is practically no literature combining these two. As management accounting as a profession has undergone significant changes in terms of its practical job scope and the expectations placed upon the controllers by the senior management, the topic is arguably relevant today. The study was conducted by firstly gaining understanding the role and expectations for a control- ler through earlier management accounting research. The onboarding process, its dimensions and tactics are examined by reviewing earlier scientific literature and understanding what the effects of choosing between different tactics are and how these either support or damage the onboarding out- comes in the context of hiring a controller. The different tactics suggested by onboarding literature are compared to the desired traits and characteristics of management accounting professionals. Fi- nally, the suggestions derived using the method mentioned above is used to compare against a case study done in a medium-sized Finnish consulting firm which has a standardised onboarding process in place and was in the process of hiring a controller at the time of writing this the thesis. The conclusions of the thesis support the existing onboarding literature, but it is important to note that the recommendations apply to specific situations and choices on the onboarding tactics have to be made, and these should be carefully aligned to the personality and the expectations being placed upon the controller hired. There are also general onboarding considerations that will improve social- isation outcomes, not specific to hiring a controller. In the case study company the director of HR was academically inclined and very well aware of the recommendations made in literature, and this seems to have contributed in the outcomes of the onboarding observed in the case study company.

Tämän tutkielman tavoitteena on kuvata vasta palkatun johdon laskentatoimen ammattilaisen, kontrollerin, onboarding-prosessia. Tavoitteena on tunnistaa onboarding-prosessin haasteet ja ehdottaa parannuksia onboarding-prosessiin, jotta siitä saatavia hyötyjä, sekä yksilölle että palkkaavalle organisaatiolle, voidaan lisätä. Tavoitteena on yhdenmukaistaa ja ymmärtää olemassa olevan onboarding-kirjallisuuden ja johdon laskentatoimen tutkimuksen välisiä suhteita ja näiden vuorovaikutusta kontrollerin roolin kannalta. Tutkimuksen motivaationa on tarjota ammatinharjoittajille hyödyllisiä ohjeita ja suosituksia siihen kuinka onboarding-prosessia voidaan tehostaa ja siitä saatavia hyötyjä korostaa. Kontrollerin roolista ja sen muutoksesta on olemassa runsaasti kirjallisuutta ja tämä on totta myös onboarding- prosessin osalta, mutta näitä yhdistelevää kirjallisuutta ei juurikaan ole olemassa. Johdon laskentatoimi on ammattina muuttunut huomattavasti sen käytänteiden, työn laajuuden ja ylimmän johdon sille asettamien vaatimuksien osalta joten aihe on kiistatta edelleen ajankohtainen. Tutkimus tehtiin ensin ymmärtämällä, aiempaan johdon laskentatoimen tutkimukseen perustuen, kontrollerin roolia ja kontrolleriin kohdistuvia odotuksia. Onboarding-prosessia, sen ulottuvuuksia ja taktiikoita tarkastellaan aiemman kirjallisuuden pohjalta. Eri taktiikoiden ja näitten välillä tehtävien valintojen vaikutusta onboarding-prosessiin tarkastellaan erityisesti kontrollerin palkkaamisen näkökulmasta. Aikaisemman onboarding tutkimuksen ehdottamia taktiikoita verrataan johdon laskentatoimen kirjallisuuden esittämiin johdon kirjanpidon ammattilaisen toivottuihin piirteisiin ja ominaisuuksiin. Lopuksi, edellä mainittua menetelmää käyttämällä saatuja ehdotuksia verrataan tapaustutkimuksessa tutkitun yrityksen käyttämään standardoituun onboarding-prosessiin. Case-yritys on keskikokoinen konsultointialan yritys joka tutkimusta tehdessä palkkasi uuden kontrollerin. Tutkielman johtopäätökset tukevat olemassa olevaa onboarding kirjallisuutta, mutta on tärkeää huomioida, että suositukset koskevat erityistilanteita ja onboarding-prosessiin liittyvien taktiikoiden valintaan vaikuttaa myös palkattavan kontrollerin persoona ja häneen kohdistuvat odotukset. Onboarding-prosessiin liittyy myös lähtökohtaisesti suosituksia, joilla on positiivinen vaikutus onboardingista saataviin tuloksiin, jotka eivät ole liitoksissa kontrollerin palkkaamiseen. Case- yrityksen henkilöstöhallinnan päällikkö oli myös merkittävän hyvin tietoinen kirjallisuudessa annetuista neuvoista ja on vaikuttanut case-yrityksen käytänteiden muodostumiseen.
Keywords: Conntroller, onboarding, the role of controller, controller function